Government Strategic Leadership In The Era Of Bureaucracy Reform - Dani Dasa Permana; Pujo Widodo; Bayu A. Yulianto; Herlina Juni Risma Saragih (CV. AFDIFAL MAJU BERKAH, 2023)
Government bureaucratic reform leads to the improvement of effective and prime professional governance in the future. The substance of government bureaucratic reform, especially leadership within departments/agencies, is very important to present good governance, given the increasing demands of society in the era of globalization which is full of challenges and competition. Leadership in this government is exciting to study, as every leader in government has a different leadership style. This research was done to identify and analyze strategic leadership in government. The method used is a qualitative approach with descriptive analysis techniques and secondary data collection through a literature review. Leadership in government requires strategic leadership that understands bureaucratic reform. Through freedom of communication and democracy in the implementation of government programs, bureaucratic reform can run well according to the expectations of society